2016
DOI: 10.3389/fnhum.2016.00016
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive and Neuroplastic Mechanisms of Novel Clinical Signs in CRPS

Abstract: Complex regional pain syndrome (CRPS) is a chronic, debilitating pain condition that usually arises after trauma to a limb, but its precise etiology remains elusive. Novel clinical signs based on body perceptual disturbances have been reported, but their pathophysiological mechanisms remain poorly understood. Investigators have used functional neuroimaging techniques (including MEG, EEG, fMRI, and PET) to study changes mainly within the somatosensory and motor cortices. Here, we provide a focused review of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 120 publications
2
50
0
Order By: Relevance
“…This was achieved by statistically predicting behaviour (RTs) from factors in the experimental design (validating the task) and from simulations of the computational model (validating the model). Specifically, RTs were modulated by both top-down (spatial change probability) and bottom-up (spatial change distance) factors, in a manner consistent with their putative role as markers of precision-weighted PEs in the brain (Kuttikat et al, 2018, 2016a). Subsequently, the computational model was able to simulate (reproduce) these condition-effects on behaviour and individual differences in these condition effects.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…This was achieved by statistically predicting behaviour (RTs) from factors in the experimental design (validating the task) and from simulations of the computational model (validating the model). Specifically, RTs were modulated by both top-down (spatial change probability) and bottom-up (spatial change distance) factors, in a manner consistent with their putative role as markers of precision-weighted PEs in the brain (Kuttikat et al, 2018, 2016a). Subsequently, the computational model was able to simulate (reproduce) these condition-effects on behaviour and individual differences in these condition effects.…”
Section: Discussionmentioning
confidence: 60%
“…Numerous behavioural studies have revealed links between pain and deficits in spatial discrimination of tactile stimuli (Förderreuther et al, 2004; Lewis and Schweinhardt, 2012; Pleger et al, 2006). Those studies, coupled with initial findings of altered somatotopic mapping of the affected (painful) limb in the primary somatosensory cortex (S1) in CRPS (Di Pietro et al, 2013; Kuttikat et al, 2016a), have motivated therapies focussed on S1 re-mapping, for example tactile discrimination training (Moseley et al, 2008). However, more recent high-resolution functional Magnetic Resonance Imaging (fMRI) studies have failed to replicate somatotopic abnormalities of S1 (Di Pietro et al, 2015; Mancini et al, 2018; van Velzen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of altered pain self-regulation might be to increase pain perception and sensitivity. Frontal cortex involvement in CRPS is supported by the effectiveness of cognitive behavioural therapy in its management [6].…”
Section: Discussionmentioning
confidence: 99%
“…Bidirectional hierarchical models based on Bayesian inference have recently been formulated for both FND36 and CRPS 45. They necessitate a rethinking for both disorders in which outdated ideas of ‘psychogenic versus neurogenic’ have to be shaken off permanently.…”
Section: The Overlaps Between Crps and Sensorimotor Fndmentioning
confidence: 99%